Femtosecond Laser in Cataract Surgery: What Makes it Worth it? or not? - Stonecipher, Karl; Parrish, Joseph; Stonecipher, Megan; Maxwell, Jamison; P. Maxwell, Donald (Journal of Ophthalmic Science, 2019)
This review is designed to look at a prospective evaluation of the use of the femtosecond laser and manual incision standard cataract surgery in one center with one surgeon focusing on visual outcomes and complications. Multiple studies support both benefits, risks, alternatives, and differences between manual capsulotomy combined with standard manual incision cataract surgery and cataract surgery employing the femtosecond laser in conjunction with routine phacoemulsification. The purpose of this study was to evaluate early postoperative outcomes using a prospective evaluation of cases from one surgeon over the course of two years from 2015-2017. The first group of cases involves 2134 eyes comparing phacoemulsification time in seconds (PT), ultrasound time in seconds (UT), and cumulative delivered energy (CDE). The second group of cases involves 1913 eyes that were Lens Opacification Classification III similar and without other ocular or lenticular abnormalities. Finally, a subgroup from the latter group (n=150) were evaluated over the course of two days and postoperative 3-hour examinations (visual acuity) were compared.
Keywords: cataract; surgery; femtosecond; laser; complications; outcomes